(untitled) (Oratio Directa, 2024)
Information credibility in digital society is increasingly challenged by the abundance of information. Truth and news accuracy are often treated merely as matters of public literacy, sharing errors, social-media effects, or legal problems rather than as questions of factual integrity and information ethics. This qualitative study uses descriptive-interpretive analysis, literature review, and virtual ethnography to examine the erosion of logos and ethics that exposes digital society to post-truth practices. Logos encompasses facts, logic, truth, and valid reasoning. In the post-truth era, truth evaluation is postponed or avoided, while falsehood can convincingly masquerade as valid argument. The study shows that post-truth rhetoric and political agendas are enabled not only by social media but also by media multiplication and the proliferation of information sources in cyberspace. These conditions blur the boundary between truth and falsehood and accelerate the circulation of disinformation.